Effective optimal control of a wind turbine system with hybrid energy storage and hybrid MPPT approach - D. Rekioua; N. Mezzai; Z. Mokrani; A. Oubelaid; K. Kakouche; P. O Logerais; Muhannad Alshareef; Mohit Bajaj; Milkias Berhanu Tuka; Sherif S. M. Ghoneim (Scientific Reports)
Abstract This research paper discusses a wind turbine system and its integration in remote locations using a hybrid power optimization approach and a hybrid storage system. Wind turbine systems’ optimization controllers operate MPPT strategies efficiently, optimizing the system’s overall performance. The proposed approach is HTb(P&O/FLC), which combines the P&O and FLC methods. This innovative hybrid MPPT strategy takes advantage of the two methods. It maximizes the wind power thus minimizing stress on the storage system. For storage, batteries are important in isolated renewable energy systems due the interminent renewable sources. Unfortunately, they have some drawbacks as lower energy density, and limited charge-discharge. Besides, supercapacitors (SCs) have advantages as quick charging and discharging and long cycle life and some drawbacks as lower energy density and specific voltage requirements. This paper proposes a hybrid storage system combining batteries and SCs. To manage the two storage technologies, an effective algorithm isproposed focusing on managing their storage systems. The findings indicate that the proposed strategy effectively maintains the state of charge (SOC) of both the batteries and SCs in the intended limits. Simulation under MATLAB and Real-time with RT-LAB were carried out to validate the proposed control approach for the wind turbine system.